COVID-19-Stresstest für die Sicherstellung der Notfallversorgung: Strategie und Maßnahmen der Notfallrettung in Berlin - Dahmen, Janosch (Anaesthesist, 2020)
BACKGROUND: The COVID-19 pandemic represents an unprecedented severe test for emergency medicine in Germany. In addition to in-hospital emergency medicine, prehospital emergency medicine has the decisive task of fully guaranteeing emergency medical healthcare. In this article the Berlin Fire Brigade shows new ways for emergency medical services to fulfil these increased responsibilities during the pandemic in prehospital emergency medicine in the State of Berlin. METHODS: A systematic presentation of the challenges and conceptional responses of preclinical emergency medicine to the COVID-19 pandemic was carried out using the example of the emergency medical services in the State of Berlin. RESULTS: The Berlin Fire Brigade has a dispatch center that coordinates all requests for assistance in the State of Berlin over the emergency telephone number 112. On average a total of 2565 emergency calls are received every 24 h, from which 1271 missions are generated. During the pandemic there was a striking increase in missions to patients with acute respiratory diseases (ARD). Of the missions 11% were carried out to patients with the suspicion of COVID-19. The duration of the emergency calls was extended on average by 1:36 min due to the additional questions in the pandemic protocol and the duration of the mission by an average of 17 min with the additional alarm keyword acute respiratory disease (ARD). CONCLUSION: The continuing pandemic reveals that tasks and responsibilities of public services in emergency rescue go far beyond the immediate medical prevention of danger to life and limb. In addition to the controller and triage functions in the integrated dispatch center of the Berlin Fire Brigade (112), the emergency and healthcare measures could be ensured. This was accomplished by comprehensive measures for situation control, situation reports and mastering situations despite the lack of alternative outpatient care options, especially in the areas of general practitioner, public health care and medical specialist practices.